The effects of total mass of seed on distribution of lead in different tissues of bean plant (Phaseolus vulgaris L.) Experimentally treated by lead - Ilić Zoran; Filipović-Trajković Radmila; Jablanović Miodrag; Biberdžić Milan (Selekcija i Semenarstvo, 2003)
In order to establish distribution of lead in different tissues of bean seed (seed coat, endosperm, embryo) depending on seed mass, treated samples (seed) by different concentration of Pb-acetate: 1O-5 M, 10-3M i 2x 10-2M. Depending on seed weight the samples derived in three groups: large (715g), middle (465g) and small (280g). Each sample contained the same number of seeds. Concentration was determined by atomic absorber (Unicam 929). At highest Pb-acetate concentration (2x10-2M) in seed with small total mass content of Pb was 1139μg/g, white in seed of 1052μg/g; in endosperm 580,6μg/g, middle 290,2μg/g and in second group 79,4μg/g. Similar pattern shows embryo but at die lower level of accumulation. On die basis of above presented results it could be concluded that concentration of Pb-acetate solution. Largest mass seed accumulate respectively less content of Pb in endosperm and embryo. Seed coat accumulated significant die larger amount of land probably embryo, in that way protects embryo. Therefore, larger bean seed are more convenient for planting in cases of potentially contamination by 1, but probably by other metals. .